The amino acid transporter SLC36A4 regulates the amino acid pool in retinal pigmented epithelial cells and mediates the mechanistic target of rapamycin, complex 1 signaling. Issue 2 (13th January 2017) - Shang, Peng; Valapala, Mallika; Grebe, Rhonda; Hose, Stacey; Ghosh, Sayan; Bhutto, Imran A.; Handa, James T.; Lutty, Gerard A.; Lu, Lixia; Wan, Jun; Qian, Jiang; Sergeev, Yuri; et al.
Summary: The dry (nonneovascular) form of age‐related macular degeneration (AMD), a leading cause of blindness in the elderly, has few, if any, treatment options at present. It is characterized by early accumulation of cellular waste products in the retinal pigmented epithelium (RPE); rejuvenating impaired lysosome function in RPE is a well‐justified target for treatment. It is now clear that amino acids and vacuolar‐type H + ‐ATPase (V‐ATPase) regulate the mechanistic target of rapamycin, complex 1 (mTORC1) signaling in lysosomes. Here, we provide evidence for the first time that the amino acid transporter SLC36A4/proton‐dependent amino acid transporter (PAT4) regulates the amino acid pool in the lysosomes of RPE. In Cryba1 (gene encoding βA3/A1‐crystallin) KO (knockout) mice, where PAT4 and amino acid levels are increased in the RPE, the transcription factors EB (TFEB) and E3 (TFE3) are retained in the cytoplasm, even after 24 h of fasting. Consequently, genes in the coordinated lysosomal expression and regulation (CLEAR) network are not activated, and lysosomal function remains low. As these mice age, expression of RPE65 and lecithin retinol acyltransferase (LRAT), two vital visual cycle proteins, decreases in the RPE. A defective visual cycle would possibly slow down the regeneration of new photoreceptor outer segments (POS). Further, photoreceptor degeneration also becomes obvious during aging, reminiscent of human dry AMD disease. Electron microscopy shows basal laminar deposits in Bruch's membrane, a hallmark of development of AMD. For dry AMD patients, targeting PAT4/V‐ATPase in the lysosomes of RPE cells may be an effective means of preventing or delaying disease progression.